Health promotion and information provision during long-term follow-up for childhood cancer survivors: A service evaluation. (17th August 2016) - Mayes, Jonathan; Brown, Morven C.; Davies, Nicola; Skinner, Roderick
ABSTRACT: Health promotion is an important component of long-term follow-up (LTFU) care for childhood cancer survivors (CCS). However, little information exists about how survivors perceive their own health promotion needs. As part of a service evaluation, 51 CCS who had previously attended the LTFU clinic took part in a single semistructured interview to seek their views on information they had received regarding late adverse effects (LAEs) of treatment, the purpose of LTFU, and the provision of health promotion information. Although most (93%) CCS were satisfied with the information received about LAEs, 37% desired further details. Over half (59%) believed that the purpose of LTFU was to screen for LAEs, whereas 31% felt that it was to check for relapse. No survivor reported health promotion to be an aim of LTFU; only 14% of CCS expected to receive healthy lifestyle advice, and fewer than 10% wanted dietary and physical activity advice. Most (88%) CCS felt that their hospital-based health care professional was best placed to give healthy lifestyle advice, but there was no consensus about the optimum timing for health promotion. CCS varied in their knowledge, needs, and wishes regarding LTFU care. The results of this evaluation strongly indicate that the profile of health promotion needs to be raised within our service and identifies issues that may be pertinent to similar services. Further research is needed to understand the views of CCS regarding health promotion and lifestyle behaviors, with the aim of tailoring and improving the delivery of effective health education to CCS.